2021
DOI: 10.3389/fendo.2021.732431
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Pancreatic Islet Transplantation Sites for the Treatment of Diabetes

Abstract: Diabetes is a complex disease that affects over 400 million people worldwide. The life-long insulin injections and continuous blood glucose monitoring required in type 1 diabetes (T1D) represent a tremendous clinical and economic burdens that urges the need for a medical solution. Pancreatic islet transplantation holds great promise in the treatment of T1D; however, the difficulty in regulating post-transplantation immune reactions to avoid both allogenic and autoimmune graft rejection represent a bottleneck i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 174 publications
0
73
0
3
Order By: Relevance
“…Recent advances in reduction of capsule thickness through conformal coating have made intraportal delivery feasible [37]; however, transplant retrievability remains an issue. Other implantation sites recently explored include epididymal fat pad, skeletal muscle, and subcutaneous (SQ) tissue [38,39]. Although preclinical studies in rodents have demonstrated efficacy, transplantation of a clinically relevant mass within these alternate sites remains an obstacle for translation.…”
Section: Glossarymentioning
confidence: 99%
“…Recent advances in reduction of capsule thickness through conformal coating have made intraportal delivery feasible [37]; however, transplant retrievability remains an issue. Other implantation sites recently explored include epididymal fat pad, skeletal muscle, and subcutaneous (SQ) tissue [38,39]. Although preclinical studies in rodents have demonstrated efficacy, transplantation of a clinically relevant mass within these alternate sites remains an obstacle for translation.…”
Section: Glossarymentioning
confidence: 99%
“…Subcutaneous transplantation is easy to operate with minimally invasive delivery and few surgical complications and is accessible to monitor and retrieve the grafts, but there is low vascular density. Other more vascularized and/or immune-privileged sites also have limitations; for instance, the omentum needs an invasive operation, and the anterior chamber of the eye is only suitable for blind patients (Cayabyab et al, 2021 ). Ideally, transplanting unencapsulated or minimally physiologically impaired, robustly functional human PSC-derived β cells without compromising the immune system of the recipient is optimal for the PSC-based islet replacement therapy, which needs constant effort.…”
Section: Discussionmentioning
confidence: 99%
“…During transplantation, islet grafts are damaged by multiple challenges, including enzyme and mechanical damage caused by the isolation process, hypoxia, inflammation, immune rejection and toxicity of immunosuppressive drugs ( 8 ). The liver is currently the preferred transplantation site because the procedure is minimally invasive, easy to perform, and has low rates of bleeding and thrombosis ( 9 ). Early inflammatory responses strongly influence islet engraftment and survival after intrahepatic transplantation.…”
Section: Introductionmentioning
confidence: 99%